2005
DOI: 10.1086/432485
|View full text |Cite
|
Sign up to set email alerts
|

Specific C‐Terminal Cleavage and Inactivation of Interleukin‐8 by Invasive Disease Isolates ofStreptococcus pyogenes

Abstract: Lethal necrotizing fasciitis caused by Streptococcus pyogenes is characterized by a paucity of neutrophils at the site of infection. Interleukin (IL)-8, which is important for neutrophil transmigration and activation, can be degraded by S. pyogenes. Blood isolates of S. pyogenes were better able to degrade human IL-8 than throat isolates. Degradation of IL-8 was the result of a single specific cleavage between 59glutamine and 60arginine within the IL-8 C-terminal alpha helix. Cleaved IL-8 reduced neutrophil ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
210
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(224 citation statements)
references
References 21 publications
11
210
0
1
Order By: Relevance
“…61,62 We detected abundant sagA transcripts; thus pel-induced virulence gene expression may be predicted, as was observed in this study for all but nga (ranked 780th in WT extracts). Therefore, these results, when coupled with the elevated expression of the neutrophil chemoattractant (interleukin-8)-cleaving SpyCEP protease (ranked 97th), 30 support the idea that coordinated, increased expression of sic, spd, sagA, speB, and spyCEP likely accounts for lack of inflammatory cells present at GAS sites in deep tissues. 63 Expression of the aforementioned GAS products, along with M1 protein, streptokinase, and the host cytolysins streptolysin O (SLO; ranked 268th) and NADase likely contributes to much of the cutaneous and subcutaneous pathologies observed in our animal model tissue infections (Supplementary Table 3; reviewed in Supplementary …”
Section: Abundant Gas Transcripts In Soft Tissue Infectionsupporting
confidence: 64%
See 1 more Smart Citation
“…61,62 We detected abundant sagA transcripts; thus pel-induced virulence gene expression may be predicted, as was observed in this study for all but nga (ranked 780th in WT extracts). Therefore, these results, when coupled with the elevated expression of the neutrophil chemoattractant (interleukin-8)-cleaving SpyCEP protease (ranked 97th), 30 support the idea that coordinated, increased expression of sic, spd, sagA, speB, and spyCEP likely accounts for lack of inflammatory cells present at GAS sites in deep tissues. 63 Expression of the aforementioned GAS products, along with M1 protein, streptokinase, and the host cytolysins streptolysin O (SLO; ranked 268th) and NADase likely contributes to much of the cutaneous and subcutaneous pathologies observed in our animal model tissue infections (Supplementary Table 3; reviewed in Supplementary …”
Section: Abundant Gas Transcripts In Soft Tissue Infectionsupporting
confidence: 64%
“…Six cotranscribed ORFs (M5005_Spy0971-6), encoding hypothetical and general stress proteins related to Gls24 of Enterococcus faecalis, were among the 20 most highly expressed GAS transcripts detected with both inoculating strains, an important finding given that Gls24 may be important for virulence in the murine invasive model of S. pneumoniae infection. 29 Other high-level GAS transcripts detected in WT-infected tissues include the chromosomal spd locus (ranked 14th) encoding a secreted DNase 17 ; sagA (ranked 28th) encoding a potent host cytolysin called streptolysin S (SLS); dppA (ranked 47th) encoding dipeptide binding protein; gap/plr (ranked 71st) and eno (ranked 117th) encoding glycolytic enzymes glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and ␣-enolase, respectively; scpA (ranked 84th) encoding C5a peptidase; spyCEP (ranked 97th) encoding an IL-8-cleaving surface proteinase 30 ; lmb (ranked 192nd) encoding a laminin-binding surface adhesin, 31 and spyA (ranked 211th) encoding an ADP-ribosyl transferring exotoxin that disrupts host cell cytoskeletal structures. 32 Several GAS regulatory genes also had highly expressed transcripts, including the repressor of class I heat shock genes hrcA 33 (ranked 15th), transcriptional regulator RofA (ranked 30th) involved in modulating adhesin expression, 8 ferric iron transport regulator PerR 34 (ranked 130th), and the TCS designated Ihk/Irr (ranked 162nd/ 288th), which is essential to GAS survival responses during PMN interactions.…”
Section: Abundant In Vivo Gas Transcriptsmentioning
confidence: 99%
“…SpyCEP is the S. pyogenes cell envelope protease that was identified by a whole-genome bioinformatics and proteomic technique (47). It is able to cleave and inactivate IL-8 and other chemokines (43,48). A number of studies, including ours, utilizing murine models have demonstrated that SpyCEP plays an important role in disease and its neutralization would be detrimental to the pathogen (9,36,42,49).…”
Section: Discussionmentioning
confidence: 96%
“…S/Ns from all strains tested were effective in destroying CXC chemokines and inhibiting chemokine-mediated neutrophil migration to some extent; however, S/Ns from a CovR/S mutant strain, 5448AP, demonstrated a dramatic effect, with a complete impediment to chemokine-mediated neutrophil migration. This strain has upregulated SpyCEP, which degrades CXC chemokines (14,27,38,39), resulting in reduced CXC-induced neutrophil transmigration and, thus, conferring resistance to GAS killing by isolated neutrophils (38). The spycep gene is negatively regulated by CovR/S, and mutation within the regulator can enhance the expression of SpyCEP $40-fold (37).…”
Section: Discussionmentioning
confidence: 99%